The impact of the COVID-19 pandemic on the research activity and working experience of clinical academics, with a focus on gender and ethnicity: a qualitative study in the UK - Carmen Soto; Jessica Elizabeth Morgan; Paul Crampton; Paul Alexander Tiffin; Gabrielle M Finn; Amelia Kehoe; Ellie Taylor; John AG Buchanan; Abisola Olatokunbo Balogun (BMJ Open)
Objective To investigate the impact of the COVID-19 pandemic on the research activity and working experience of clinical academics, with a focus on gender and ethnicity.Design Qualitative study based on interviews and audio/written diary data.Setting UK study within clinical academia.Participants Purposive sample of 82 clinical academics working in medicine and dentistry across all career stages ranging from academic clinical fellows and doctoral candidates to professors.Methods Qualitative semistructured interviews (n=68) and audio diary data (n=30; including 16 participants who were also interviewed) collected over an 8-month period (January–September 2020), thematically analysed.Results 20 of 30 (66.6%) audio diary contributors and 40 of 68 (58.8%) interview participants were female. Of the participants who disclosed ethnicity, 5 of 29 (17.2%) audio diary contributors and 19/66 (28.8%) interview participants identified as Black, Asian or another minority (BAME). Four major themes were identified in relation to the initial impact of COVID-19 on clinical academics: opportunities, barriers, personal characteristics and social identity, and fears and uncertainty. COVID-19 presented opportunities for new avenues of research. Barriers included access to resources to conduct research and the increasing teaching demands. One of the most prominent subthemes within ‘personal characteristics’ was that of the perceived negative impact of the pandemic on the work of female clinical academics. This was attributed to inequalities experienced in relation to childcare provision and research capacity. Participants described differential experiences based upon their gender and ethnicity, noting intersectional identities.Conclusions While there have been some positives afforded to clinical academics, particularly for new avenues of research, COVID-19 has negatively impacted workload, future career intentions and mental health. BAME academics were particularly fearful due to the differential impact on health. Our study elucidates the direct and systemic discrimination that creates barriers to women’s career trajectories in clinical academia. A flexible, strategic response that supports clinical academics in resuming their training and research is required. Interventions are needed to mitigate the potential lasting impact on capacity from the pandemic, and the potential for the loss of women from this valuable workforce.